Clinical Insights of Acute Invasive Fungal Rhinosinusitis in a Tertiary Care Center in Gujarat - Dr.Nazmabanu M. Sheliya, Dr. Saloni Shah, Dr. Sanket Shah (South Eastern European Journal of Public Health, 2025)
Background and Aim: Acute invasive fungal rhinosinusitis (AIFRS) is a severe, rapidly progressive infection that primarily affects immunocompromised individuals, often leading to significant morbidity and mortality. The disease involves various fungal species, including Mucor, Rhizopus, Aspergillus, and Scedosporium, and can rapidly extend from the paranasal sinuses to adjacent structures, such as the orbit and brain. The main aim of the study was to evaluate about the different clinical and epidemiological features of AIFRS patients in tertiary care centre. Material and Methods: A retrospective observational study was conducted at a tertiary care center in South Gujarat for the duration of 1 year. A total of 176 patients diagnosed with AIFRS were included. Clinical features, presenting symptoms, and comorbidities were assessed, with a particular focus on the impact of underlying conditions such as diabetes mellitus. Results: The most common presenting symptoms were facial pain (51.7%), palatal involvement (35.23%), and nasal obstruction/discharge (32.39%). The study also highlighted the high prevalence of diabetes mellitus (54.55%) as a major risk factor. Other symptoms included diminished vision (17.64%) and proptosis (13.23%). Most of the patients exhibited multiple comorbidities, further complicating the disease progression. Conclusion: Early diagnosis and intervention are crucial for improving outcomes in AIFRS patients. A multidisciplinary approach, including timely surgical debridement and antifungal therapy, is essential to mitigate the rapid progression of this life-threatening infection. The study highlights the need for increased clinical awareness, especially in patients with diabetes or other immunosuppressive conditions.